2009
DOI: 10.1002/lt.21681
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of liver transplantation in the management of acute liver failure: Comparison between acetaminophen and non-acetaminophen etiologies

Abstract: Liver transplantation (LT) may be life-saving in severe acute liver failure (ALF). The aim of this study was to compare the utilization of LT in acetaminophen and non-acetaminophen ALF. Between 1992 and 2006, 469 patients with ALF were admitted, and 104 underwent LT. Acetaminophen was the most common etiology, but LT proceeded more frequently in the non-acetaminophen cohort (acetaminophen: 45/326 patients received LT, 13.8%; non-acetaminophen: 59/143 patients received LT, 41.3%; P Ͻ 0.01). A retrospective anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 40 publications
2
88
1
2
Order By: Relevance
“…Laboratory investigations were repeated at daily intervals or more frequently in patients with rapidly progressive liver failure. Patients admitted to the SLTU are managed using a standard protocol as previously described, with patients with paracetamol poisoning treated with a continuous NAC infusion (6.25 mg kg -1 h -1 ) until the international normalized ratio (INR) is less than 2 [11]. The main therapeutic goals of this protocol have remained similar over the 16 years of this cohort study.The modified King's College Hospital poor prognostic criteria (KCC) are used in this unit and throughout the UK to determine patients who will most likely die without OLT [12].…”
Section: Patientsmentioning
confidence: 99%
“…Laboratory investigations were repeated at daily intervals or more frequently in patients with rapidly progressive liver failure. Patients admitted to the SLTU are managed using a standard protocol as previously described, with patients with paracetamol poisoning treated with a continuous NAC infusion (6.25 mg kg -1 h -1 ) until the international normalized ratio (INR) is less than 2 [11]. The main therapeutic goals of this protocol have remained similar over the 16 years of this cohort study.The modified King's College Hospital poor prognostic criteria (KCC) are used in this unit and throughout the UK to determine patients who will most likely die without OLT [12].…”
Section: Patientsmentioning
confidence: 99%
“…A recent study from the UK suggested that OLT is a more favorable approach to managing patients with non-APAP induced ALF compared to patients with APAP induced ALF. This was predominantly due to the frequent psychosocial contraindications in patients with APAP induced ALF (Simpson et al, 2009).…”
Section: Etiologymentioning
confidence: 99%
“…In the United Kingdom, about 30% of patients initially considered for OLT ultimately become untransplantable following the development of complications (i.e., cerebral edema, sepsis, hemodynamic abnormalities, multiorgan system failure) (Bernal et al, 1998). Additionally, many patients have medical or psychosocial contraindications to transplantation, including irreversible brain injury, underlying cardiovascular disease, infection/sepsis, alcohol or drug abuse, poorly controlled psychiatric disease, or inadequate family support (Simpson et al, 2009). Thus, it is important to identify and delist patients who are too ill to benefit from OLT.…”
Section: Prognosis and Prognostic Modelsmentioning
confidence: 99%
“…Its overdose, however, can be life threatening, causing severe liver and kidney damage (2)(3)(4)(5). In Western countries, acetaminophen-induced hepatotoxicity is a leading cause of acute liver failure requiring liver transplantation (6). Due to a widespread availability of acetaminophen and potentially lethal consequences of its overdose, the mechanisms of acetaminophen hepatotoxicity have been in focus of a large number of investigations (7).…”
mentioning
confidence: 99%